Transforming Teachers Through Project-Based Learning: A Systematic Literature and Network Analysis - Indah Murtini; Eveline Siregar; Robinson Situmorang; Imam Fitri Rahmadi (South Sulawesi Education Development (SSED), 2025)
This study employed an integrated Systematic Literature and Network Analysis (SLNA) approach to examine project-based learning teacher training models and their role in facilitating teacher transformation. Following PRISMA 2020 guidelines, we systematically reviewed 18 empirical studies (2020-2024) from Scopus database across diverse educational contexts in Asia and Europe, complemented by VOSviewer bibliometric analysis of 330 keyword co-occurrence networks. Results identified five essential training components: theoretical understanding, hands-on practice, structured reflection, collaborative learning, and sustained mentoring support. Teacher transformation progressed across three dimensions—pedagogical competence, teaching self-efficacy, and classroom implementation skills—with persistent challenges in classroom management, time allocation, and curriculum alignment. Bibliometric analysis positioned teacher transformation research at the convergence of pedagogical innovation, professional development theory, and technological integration, with COVID-19 as a catalytic network node and artificial intelligence representing the most recent high-impact frontier. Findings indicate effective PBL teacher training requires phase-based, scaffolded programs embedding authentic practice within collaborative professional learning communities and sustained institutional support.